The Correlation between Students’ L2 Motivation and Their EFL Proficiency - Purnama Cahya (Universitas Cokroaminoto Palopo, 2017)
This study is intended to find the correlation between students L2 motivation and their EFL proficiency. The Instruments used in this current study involved questionnaire and test. The questionnaire is used to measure the students’ motivation and the test was used to reveal student’s EFL proficiency score. The current study involves 195 college students from four universities in Malang. The result of analysis shows that there is a significant correlation between L2 motivation and the students’ EFL proficiency. It is proved by the test of hypothesis in which P Value (0.002) is lower than Alfa (α = 0.01). The result implies the increase in students’ motivation can be a prediction of the increase of students’ EFL proficiency. The students who are strongly motivated in learning English are most probably achieve better in their EFL proficiency.